Low‐Temperature Atomic Layer Deposition Synthesis of Vanadium Sulfide (Ultra)Thin Films for Nanotubular Supercapacitors - Raul Zazpe; Marcela Sepúlveda; Jhonatan Rodriguez‐Pereira; Ludek Hromadko; Jan Michalicka; Eva Kolíbalová; Michal Kurka; Sitaramanjaneya M. Thalluri; Hanna Sopha; Jan M. Macak (Small Structures, 2024)
Herein, the synthesis of vanadium sulfide (VxSy) by atomic layer deposition (ALD) based on the use of tetrakis(dimethylamino) vanadium (IV) and hydrogen sulfide is presented for the first time. The (ultra)thin films VxSy are synthesized in a wide range of temperatures (100–225 °C) and extensively characterized by different methods. The chemical composition of the VxSy (ultra)thin films reveals different vanadium oxidation states and sulfur‐based species. Extensive X‐ray photoelectron spectroscopy analysis studies the effect of different ALD parameters on the VxSy chemical composition. Encouraged by the rich chemistry properties of vanadium‐based compounds and based on the variable valences of vanadium, the electrochemical properties of ALD VxSy (ultra)thin films as electrode material for supercapacitors are further explored. Thereby, nanotubular composites are fabricated by coating TiO2 nanotube layers (TNTs) with different numbers of VxSy ALD cycles at low temperature (100 °C). Long‐term cycling tests reveal a gradual decline of electrochemical performance due to the progressive VxSy thin films dissolution under the experimental conditions. Nevertheless, VxSy‐coated TNTs exhibit significantly superior capacitance properties as compared to the blank counterparts. The enhanced capacitance properties exhibited are derived from the presence of chemically stable and electrochemically active S‐based species on the TNTs surface.